2021
DOI: 10.4143/crt.2020.123
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Total Metabolic Tumor Volume and Total Lesion Glycolysis Measured on 18F-FDG PET-CT Predict Outcomes in T-Cell Lymphoblastic Lymphoma

Abstract: Purpose There is no optimal prognostic model for T-cell lymphoblastic lymphoma (T-LBL). Here, we discussed the predictive value of total metabolic tumor volume (TMTV) and total lesion glycolysis (TLG) measured on 18F-fluorodeoxyglucose positron emission tomography–computed tomography (PET-CT) in T-LBL.Materials and Methods Thirty-seven treatment naïve T-LBL patients with PET-CT scans were enrolled. TMTV was obtained using the 41% maximum standardized uptake value (SUVmax) threshold method, and TLG was measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…The baseline SUV max , TLG and MTV of lymph nodes were related to OS in lymphoma, including HL, diffuse Large B-cell lymphoma, follicular lymphoma, peripheral T lymphocyte lymphoma, extranodal NK/T lymphoma, etc. (11,40). Besides, elevated IL-6 indicates strong "inflammatory storm, " suggesting the internal environment disturbance and a high mortality rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The baseline SUV max , TLG and MTV of lymph nodes were related to OS in lymphoma, including HL, diffuse Large B-cell lymphoma, follicular lymphoma, peripheral T lymphocyte lymphoma, extranodal NK/T lymphoma, etc. (11,40). Besides, elevated IL-6 indicates strong "inflammatory storm, " suggesting the internal environment disturbance and a high mortality rate.…”
Section: Discussionmentioning
confidence: 99%
“…18 F-FDG PET/CT is a whole-body scan widely used in many diseases, such as infection, malignant disease, and rheumatic immunity disease (10). In varieties of lymphoma, it is used in differential diagnosis, treatment decision, response evaluation and prognosis prediction (10,11). 18 F-FDG PET/CT is better than conventional radiography, as it can display the extranodal lesions better and measure the metabolism in semi-quantitative analysis (12).…”
Section: Introductionmentioning
confidence: 99%
“…Feng et al. indicated that baseline SUV max measured on 18 F-FDG in T-cell lymphoblastic lymphoma was significantly related to PFS and OS ( 35 ). Okuyucu et al.…”
Section: Discussionmentioning
confidence: 99%
“…7 It also has value in predicting diagnosis, evaluating treatment response, and providing prognostic information for lymphoma and other solid tumors. 8 11 To date, the quantitative parameters of 18 FDG-PET/CT have been investigated in several lymphoma entities, including PMBCL, illustrating its prognostic value. 12 14 …”
Section: Introductionmentioning
confidence: 99%
“…7 It also has value in predicting diagnosis, evaluating treatment response, and providing prognostic information for lymphoma and other solid tumors. [8][9][10][11] To date, the quantitative parameters of 18 FDG-PET/CT have been investigated in several lymphoma entities, including PMBCL, illustrating its prognostic value. [12][13][14] In the current study, we retrospectively reviewed a cohort of patients with PMBCL to provide insights into treatment modalities and the prognostic utility of certain clinical characteristics, as well as clarify the features of 18 FDG-PET/CT.…”
Section: Introductionmentioning
confidence: 99%